1998
DOI: 10.1002/(sici)1098-237x(199804)82:2<181::aid-sce4>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The inclusion of multicultural material in middle school science teachers' resource manuals

Abstract: We examined and categorized multicultural teaching information found in middle school science teachers' resource manuals to determine how multicultural information relates to guidelines for teaching in multicultural classrooms. A content analysis of 21 teachers' editions of middle school science textbooks determined: (a) the extent of multicultural content; (b) the distribution within foundational knowledge categories; and (c) the relationship to the science content. Data were identified through the use of ERI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Unfortunately, even when they are convinced of this, there continues to be little help for them in their implementation strategies. Heikkinen and Eide (1998) reviewed teacher resource manuals for twenty-one of the most popular middle school science textbooks in the US and found that:…”
Section: Résumémentioning
confidence: 99%
“…Unfortunately, even when they are convinced of this, there continues to be little help for them in their implementation strategies. Heikkinen and Eide (1998) reviewed teacher resource manuals for twenty-one of the most popular middle school science textbooks in the US and found that:…”
Section: Résumémentioning
confidence: 99%
“…Two types of science texts are most commonly found in elementary classroomstextbooks, created by the publishing industry, and trade books, generally the work of a single author, marketed to the general public. Although science textbooks have received criticisms for years on a host of topics (e.g., AAAS, 1989;Eide & Heikkinen, 1998;Hubisz, 2001;Mallinson, Sturm, & Patton, 1950;Wellington, 2001), the fact remains that they are used by the large majority of elementary school teachers (Weiss, Banilower, McMahon, & Smith, 2001). Thus, it was reasonable for Newton and colleagues to turn to textbooks as they sought to locate another source for explanations in science classrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Eide and Heikkinen 16 investigated the inclusion of multicultural material in middle school science teachers' resource texts. Noting that teacher resource texts (often referred to as teachers' editions) are highly used instructional resources, the authors analyzed the extent of multicultural content in twenty-one teachers' editions of middle school science texts.…”
Section: Bias In Science Textbooksmentioning
confidence: 99%
“…They found that multicultural content was present in only small amounts in middle school teachers' editions. This finding led Eide and Heikkinen 16 to recommend additional inclusion of this important material in the science resource texts. They posited that it would be very difficult for teachers to teach multiculturally using their resource books given the sparse representation of this content.…”
Section: Bias In Science Textbooksmentioning
confidence: 99%